Distribution and potential toxicity of benthic harmful dinoflagellates in waters of Florida Bay and the Florida Keys. (March 2020) - Accoroni, Stefano; Totti, Cecilia; Romagnoli, Tiziana; Giulietti, Sonia; Glibert, Patricia M.
Abstract: Few studies have been carried out on benthic dinoflagellates along the Florida Keys, and little is known about their distribution or toxicity in Florida Bay. Here, the distribution and abundance of benthic dinoflagellates was explored in northern and eastern Florida Bay and along the bay and ocean sides of the Florida Keys. Isolates were brought into culture and their toxicity was tested with oyster larvae bioassays. Seven genera were detected, including Prorocentrum, Coolia, Ostreopsis, Amphidinium, Gambierdiscus, Fukuyoa (all included potentially toxic species) and Sinophysis . In general, distribution increased with water temperature and nutrient availability, especially that of phosphate. This study documented the first record of Coolia santacroce in the Florida Keys. Potential toxic effects of Gambierdiscus caribaeus, the abundance of which exceeded 1000 cells g −1 fw at some sites, were established using oyster larvae as a bioassay organism. These findings suggest a potential risk of ciguatera fish poisoning in this area. Highlights: Several genera of potentially toxic benthic dinoflagellates were detected. BHAB community were affected by temperature and nutrient availability (mainly P). Larval bioassay tests revealed clear toxic effects for Gambierdiscus caribaeus . Gambierdiscus abundances sometimes exceeded 1000 cells g −1 fw, posing a risk of CFP. This is the first record of Coolia santacroce in the Florida Keys.